Advice for Decision Makers Based on an Electronic Health Record Evaluation at a Program for All-inclusive Care for Elders Site - Sockolow, P.S.; Weiner, J.P.; Bowles, K.H.; Abbott, P.; Lehmann, H.P. (Applied Clinical Informatics, 2011)
Objective: Provide evidence-based advise to “Program of All-inclusive Care for the Elderly” (PACE) decision makers considering implementing an electronic health record (EHR) system, drawing on the results of a mixed methods study to examine: (1) the diffusion of an EHR among clinicians documenting direct patient care in a PACE day care site, (2) the impact of the use of the EHR on the satisfaction levels of clinicians, and (3) the impact of the use of the EHR on patient functional outcomes.Methods: Embedded mixed methods design with a post-test design quantitative experiment and concurrent qualitative component. Quantitative methods included: (1) the EHR audit log used to determine the frequency and timing during the week of clinicians’ usage of the system; (2) a 22-item clinician satisfaction survey; and (3) a 16-item patient functional outcome questionnaire related to locomotion, mobility, personal hygiene, dressing, feeding as well the use of adaptive devices. Qualitative methods included observations and open-ended, semi-structured follow-up interviews. Qualitative data was merged with the quantitative data by comparing the findings along themes. The setting was a PACE utilizing an EHR in Philadelphia: PACE manages the care of nursing-home eligible members to enable them to avoid nursing home admission and reside in their homes. Participants were 39 clinicians on the multi-disciplinary teams caring for the elders and 338 PACE members.Results: Clinicians did not use the system as intended, which may help to explain why the benefits related to clinical processes and patient outcomes as expected for an EHR were not reflected in the results. Clinicians were satisfied with the EHR, although there was a non-significant decline between 11 and 17 months post implementation of the EHR. There was no significant difference in patient functional outcome the two time periods. However, the sample size of 48 was too small to allow any conclusive statements to be made. Interpretation of findings underscores the importance of the interaction of workflow and EHR functionality and usability to impact clinician satisfaction, efficiency, and clinician use of the EHR.Conclusion: This research provides insights into EHR use in the care of the older people in community-based health care settings. This study assessed the adoption of an EHR outside the acute hospital setting and in the community setting to provide evidence-based recommendations to PACE decision makers considering implementing an EHR.
Keywords: Evaluation studies; technology evaluation; clinical information systems; patient care team; aged